Towards a Novel Silk-based Biosensing Platform with Broad Biomedical Utility: A Multifaceted Approach. - Brenckle, Mark Allen. (Tufts Archival Research Center, 2005)
As a biomaterial, silk fibroin protein possesses a number of desirable characteristics, including biocompatibility and remarkable strength, which make it ideal for a number of biosensing applications. Herein, we take a broad look at a number of the important components of developing such a sensor, including conjugating IgG antibodies to the silk substrate as a biosignal, the materials aspects of producing sensor-films, patterned film and metamaterial transduction mechanisms, and simple utility enhancements for the films. It is our expectation that conjugation will be possible using conventional conjugation chemistries, and that applying transduction mechanisms as an intermediate assay will give additional insight into the conjugation scheme that was not previously available. By examining these issues and their interrelatedness, we hope to be able to both extend the state of this project in a number of areas, and determine where the largest areas of difficulty are in developing biosensors of this nature.